Intensive X-ray source optimization - Bochek, G.L.; Kulibaba, V.I.; Maslov, N.I.; Ovchinnik, V.D. (Вопросы атомной науки и техники, 2005)
Possibility of optimization of an intensive source of the electron radiation in crystals based on the Compton scattering of X-radiation is considered.